IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH COLLABORATIVE WRITING - Sidabalok, Nurhasanah -; Ginting, Siti Aisah (Universitas Negeri Medan, 2014)
Abstract The main objective of this study is to know how effective the use of Collaborative Writing in teaching writing descriptive texts is. So this final project mainly aims at determining the effectiveness of using Collaborative Writing in teaching writing descriptive texts. This study was conducted under the consideration that the students often get difficulties in describing something. In order to achieve the objective of the study, the writer designed an action research. The population of this study was the second grade students of SMP Negeri 29 Medan. The number of the subjects of this study was 37 students. During the research, the students becoming the subjects were taught by using Collaborative Writing in teaching writing descriptive texts. There were two cycles in this action research. Each cycle consisted of four phases. Before giving treatments in those two cycles, the students were given pre-test. After each treatment in each cycle, the students were tested. And the last, they were given post-test and questionnaire. The main purpose of conducting it was to find out the validity and the reliability of the test as instrument. The result of this research showed that the students™ ability in writing descriptive texts improved after a series of treatments given in the cycles. It can be seen by comparing the means of their tests. The mean score for the pre-test was 53.92, the mean score for test 1 was 70.27, while the mean score for the post-test was 80.08. It is clear that after applying Collaborative Writing in each treatment, the mean of each test improves and gets better. The use of Collaborative Writing technique is one of the ways to make students interest in studying English especially writing descriptive text. Keywords: Achievement, Writing, Descriptive Text, Collaborative Writing